The impacts of non traditional exports on income, child health and education in rural Zambia - Balat, Jorge (2007)
This paper investigates the impacts of non-traditional exports on household outcomes in rural Zambia. Traditionally, Zambia has been an exporter of copper and only recently has the increase in agricultural exports been observed. Potential products include cotton, tobacco, fruits, vegetables, food processing, and textiles. International markets for these nontraditional exports have generated new opportunities for vulnerable and poor households. While the current literature focuses more on the income dimension of adjustment, in this paper we explore non-monetary outcomes as well. Concretely, we study the impacts of export opportunities on income, child health and education in rural households. We find positive income differentials of households involved in market agriculture over subsistence agriculture. While we find that children living in households involved in cotton tend to show better longrun anthropometric outcomes, no systematic differences are observed in households engaged in other agricultural activities. Finally, we find that households in market agriculture tend to educate their children more than households in subsistence. There is some evidence that boys are benefited more than girls.